MATEMATIKA DAN KEARIFAN LOKAL: NOKEN SEBAGAI MEDIA EDUKATIF DI TANAH PAPUA - Gombo, Mikaus (Haga : Jurnal Pengabdian Kepada Masyarakat, 2024)
This community service activity aims to enhance students’ understanding of mathematics in the Papua region through the integration of local culture, particularly noken, into mathematics education. Using an ethnomathematics approach, noken, which contains mathematical elements such as weaving patterns, symmetry, and geometry, is employed as a medium to introduce mathematical concepts that are more contextual and relevant to students’ daily lives. This activity involves primary school teachers and students in Papua, with training and guidance on how to use noken as a teaching tool. Evaluation results show a significant improvement in students’ understanding of mathematics, as well as increased teacher involvement and creativity in developing culturally-based learning materials. However, challenges such as limited instructional time pose obstacles to full implementation. This activity is expected to empower the community through education, preserve the noken culture, and strengthen students’ mathematical literacy in a contextual and meaningful way.